PERANCANGAN DAN ANALISIS STRUKTUR BAJA PENYANGGA TANGKI AIR YANG DITINGGIKAN KAPASITAS 100 M³ PRODUK PT. PELANGI INDOKARYA - M. Hilmy Syahfata; Mohamad Hakam; Priyo Agus Setiawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Industries engaged in manufacturing require a water supply. The required clean water capacity of 100 m³ is used to meet industrial needs, with the fulfillment of this amount having a positive impact on the smooth production process and related aspects for daily needs. The water tank is a water storage container with the aim of fulfilling the water supply at a certain height to provide pressure and facilitate the water distribution system. This research designs a steel structure supporting a water tank to support these needs. The tank tower structure is designed by considering several loads that will be received. The design method used is the Ulrich method, which involves creating three design concepts from which one of the best designs will be selected according to the selection criteria. The design of the steel structure supporting the water tank is carried out through strength analysis with Ansys Mechanical APDL software to determine the amount of stress obtained from the combination of loading received. This research results the steel structure supporting the water tank in the selected design concept shows a maximum stress value of 6.5 kg/mm2. The value obtained is still below the maximum allowable stress value of 16.67 kg/mm2. The total budget for steel structural materials in the form of profiles and plates is Rp 1,197,129,128.00.